2013
DOI: 10.1136/bjophthalmol-2012-302784
|View full text |Cite
|
Sign up to set email alerts
|

Management of complicated multirecurrent pterygia using multimicroporous expanded polytetrafluoroethylene

Abstract: AimsTo evaluate the efficiency of multimicroporous expanded polytetrafluoroethylene (e-PTFE) insertion in complicated multirecurrent pterygia.MethodsA total of 62 eyes from 62 patients with a multirecurrent pterygium associated with symblepharon or motility restriction-related binocular diplopia were recruited. All eyes underwent pterygia excision followed by application of 0.033% mitomycin C, amniotic membrane transplantation and conjunctival limbal autograft. Multimicroporous e-PTFE was then inserted intraop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…Recently, the intraoperative insertion of expanded polytetrafluoroethylene (e-PTFE), a biocompatible fluoropolymer used for soft tissue reconstruction, has been shown to significantly reduce pterygium recurrence when transplanted between the amniotic membrane and conjunctiva in multirecurrent pterygium. 169 Once surgical excision has been performed, adjunctive therapy is used to prevent pterygium recurrence. The most common therapies are Mitomycin C (MMC), b-radiation, and 5-fluoruroacil .…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, the intraoperative insertion of expanded polytetrafluoroethylene (e-PTFE), a biocompatible fluoropolymer used for soft tissue reconstruction, has been shown to significantly reduce pterygium recurrence when transplanted between the amniotic membrane and conjunctiva in multirecurrent pterygium. 169 Once surgical excision has been performed, adjunctive therapy is used to prevent pterygium recurrence. The most common therapies are Mitomycin C (MMC), b-radiation, and 5-fluoruroacil .…”
Section: Treatmentmentioning
confidence: 99%
“…Multimikroporöses Einbringen der e-PTFE-Membran könnte Ansatzpunkte zu neuen Therapien zur Behandlung vom komplizierten, mehrfach rezidivierenden Pterygia liefern [5,15].…”
Section: Methodenunclassified
“…A recent study for patients with multi-recurrent pterygia found that the implantation of multi-microporous expanded polytetrafluoroethylene between AM and conjunctiva in conjunction with mitomycin C and a conjunctival limbal autograft led to significantly lower recurrence rates from 25% to 3.3% (p = 0.027) and also reduced symblepharon (p = 0.024), motility restriction (p = 0.027), and hyperemia (p < 0.001) [16].…”
Section: Surgical Techniquementioning
confidence: 99%
“…This led to a significant reduction in recurrence rates [2,6]. A recent Cochrane meta-analysis of 1947 eyes of 1866 patients revealed superiority of CAG over AM with a risk ratio (RR) for recurrence of pterygium (primary and recurrent) of 0.53 (95% confidence interval [CI]: 0.33-0.85; p = 0.009) at 6-month follow-up and recurrence rates from 3.33% to 16.7% in the CAG and 2.6% to 42.3% in the AM group [6]. Therefore, thorough pterygium and Tenon's tissue removal combined with a CAG transplantation is currently considered the gold standard surgical procedure.…”
Section: Surgical Techniquementioning
confidence: 99%